Microglia in the context of multiple sclerosis - Zhang, Xue; Chen, Fang; Sun, Mingyue; Wu, Nan; Liu, Bin; Yi, Xiangming; Ge, Ruli; Fan, Xueli (Frontiers in Neurology, 2023)
Multiple sclerosis (MS) is an inflammatory and neurodegenerative disease that commonly results in nontraumatic disability in young adults. The characteristic pathological hallmark of MS is damage to myelin, oligodendrocytes, and axons. Microglia provide continuous surveillance in the CNS microenvironment and initiate defensive mechanisms to protect CNS tissue. Additionally, microglia participate in neurogenesis, synaptic refinement, and myelin pruning through the expression and release of different signaling factors. Continuous activation of microglia has been implicated in neurodegenerative disorders. We first review the lifetime of microglia, including the origin, differentiation, development, and function of microglia. We then discuss microglia participate in the whole processes of remyelination and demyelination, microglial phenotypes in MS, and the NF-κB/PI3K-AKT signaling pathway in microglia. The damage to regulatory signaling pathways may change the homeostasis of microglia, which would accelerate the progression of MS.